Unraveling the multiscale comovement of green bonds and structural shocks: An oil-driven analysis - Mobeen Ur, Rehman (2024)
This paper examines the multiscale comovement between the green bonds issued in developed countries and international oil-driven shocks. We extracted the oil shocks using a structural vector autoregressive model. The countries in our analysis comprised the UK, the US, Japan, Canada, Australia, and Europe, with the data being captured from November 28, 2008 to June 11, 2021. We applied the wavelet technique to examine the returns comovement across time and frequency as a form of bivariate and multivariate analysis. Our results highlight a limited connection between the returns of green bonds and the international oil market, with Norway and Sweden exhibiting strong comovement across low frequencies. We posit that during crisis periods, the correlation between green bond returns and oil returns varies. The findings of this study have several implications for policymakers and investors with an interest in both oil futures and green bonds.